PENGARUH KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PT. VISION SOLUSINDO PRATAMA - Hendrayani, Hendrayani (Sekolah Tinggi Ilmu Ekonomi Riau, 2018)
This research was conducted at PT. Vision Solusindo Pratama with the aim to mengatahui influence job satisfaction on employee performance PT. Vision Solusindo Pratama. Population in this research is all employees of PT. Vision Solusindo Pratama totaling 48 people. While the data analysis used is test reliability and simple linear regression test and coefficient of determination test. Hypothesis testing using t test. The results of this study using the help of SPSS. From SPSS testing found that there is a positive and significant relationship between job satisfaction with employee performance PT. Vision Solusindo Pratama